Development and refinement of the open dialog adherence protocol in complex mental health care - Lotmore, Melissa; Ziedonis, Douglas; Alvarez Monjaras, Mauricio; Hopfenbeck, Mark; Razzaque, Russell; Wilson, Emily; Pilling, Stephen (Frontiers in Psychology, 2023)
Introduction. Open Dialogue (OD) is a both a therapeutic practice and a service delivery model that offers an integrated response to mental health care through mobilising resources within the service user’s family and community networks through joint network meetings. Therapist adherence is a crucial to the effective delivery of interventions. A key way to measure this is through structured observation tools. Aims. The aim of this research project is to develop and refine The Dialogic Practice Adherence Scale, for use in OD research trials in the UK. Methods. This study was a mixed methods approach to the development of an OD practitioner adherence measure. Initial steps involved meetings and discussions with experts and a review of the literature. Content validation studies were completed using a modified Delphi technique. To assess reliability of the measure, OD network meetings were audio-recorded, and tapes were rated by two independent researchers. Inter-rater reliability and internal consistency were assessed through quantitative approaches assessing variance. Results. Results provide a description of how the OD Adherence Manual was developed in collaboration. Validation surveys showed high levels on consensus among experts in the field on the key elements of OD network meetings. Inter-rater reliability for the total score was excellent and internal consistency analyses suggest the scale is highly reliable. Discussion. The scale presented here is an initial attempt at rating practitioner adherence in OD network meetings. It provides encouraging evidence that this can be done with strong validity and reliability and can be completed by a range of raters with varying levels of clinical experience.